2014
DOI: 10.1002/jbmr.2285
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Acute Exercise on Undercarboxylated Osteocalcin and Insulin Sensitivity in Obese Men

Abstract: Acute exercise improves insulin sensitivity for hours after the exercise is ceased. The skeleton contributes to glucose metabolism and insulin sensitivity via osteocalcin (OC) in its undercarboxylated (ucOC) form in mice. We tested the hypothesis that insulin sensitivity over the hours after exercise is associated with circulating levels of ucOC. Eleven middle-aged (58.1 AE 2.2 years mean AE SEM), obese (body mass index [BMI] ¼ 33.1 AE 1.4 kg/m 2 ) nondiabetic men completed a euglycemic-hyperinsulinemic clamp … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
97
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 89 publications
(107 citation statements)
references
References 39 publications
7
97
0
3
Order By: Relevance
“…The ϳ6% impairment in the postexercise enhancement of insulin sensitivity is a small yet statistically significant effect determined via the hyperinsulinemic euglycemic clamp, a technique commonly used as a gold-standard measurement of IS. Although we did not measure resting vs. postexercise IS, it has been shown previously that whole body IS was elevated by 32% 18 h after exercise in sheep (24) and to a similar degree 3 h postexercise in an older overweight population (19). Since exercise is an effective means of improving IS for not only healthy individuals but those with insulin resistance (36), it can be suggested that any impairment to this beneficial effect is clinically relevant.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…The ϳ6% impairment in the postexercise enhancement of insulin sensitivity is a small yet statistically significant effect determined via the hyperinsulinemic euglycemic clamp, a technique commonly used as a gold-standard measurement of IS. Although we did not measure resting vs. postexercise IS, it has been shown previously that whole body IS was elevated by 32% 18 h after exercise in sheep (24) and to a similar degree 3 h postexercise in an older overweight population (19). Since exercise is an effective means of improving IS for not only healthy individuals but those with insulin resistance (36), it can be suggested that any impairment to this beneficial effect is clinically relevant.…”
Section: Discussionmentioning
confidence: 92%
“…Muscle samples were obtained from the middle third of the vastus lateralis muscle using the percutaneous needle biopsy technique (19). After injection of a local anaesthetic into the skin and fascia (1% Xylocaine; Astra Zeneca), a small incision was made and a muscle sample taken (ϳ100 -200 mg) using a Bergström biopsy needle with suction.…”
Section: Muscle Biopsy Samplingmentioning
confidence: 99%
See 1 more Smart Citation
“…Insulin-stimulated AS160 phosphorylation (p-AS160) and glucose uptake have been studied in humans after onelegged exercise (86,118 (118). However, high-intensity interval cycle ergometry led to greater glucose disposal during a euglycemic hyperinsulinemic clamp without elevated muscle p-AS160 Thr 642 at 3 h postexercise (72). Greater AS160 phosphorylation has often, but not always, been found after exercise that improved insulin sensitivity.…”
Section: Potential Mediatorsmentioning
confidence: 99%
“…11,12 Acute exercise also increases OC and the undercarboxylated form of OC in obese men, and this increase is related to a reduction in serum glucose levels and higher insulin sensitivity as measured by the use of an hyperinsulinaemic-euglycaemic clamp (HEC). 13,14 Using these same patients, we now hypothesise that, (a) at rest, BRMs will be suppressed during a 2 h HEC in obese men, and (b) exercise prior to insulin clamping will increase BRMs and that in turn will prevent the predicted suppression of BRMs in response to the HEC. In the current study, we therefore use the HEC as a tool to deliver and then examine the effects of insulin and glucose on BRMs.…”
Section: Introductionmentioning
confidence: 98%